(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The purpose of this study was to determine whether patients with class 2 skeletal malocclusion in a private dental hospital had skeletal discrepancies.Materials and methods: This was a descriptive, retrospective study, and the dental information archiving software was used to collect all the data from the patients who attended the dental clinics at Saveetha Dental College, SIMATS, Chennai, India (DIAS). March 2020 through March 2021 saw the collection of patient records. We gathered and tabulated the data. The gathered data underwent additional processing, was entered into Microsoft Excel, and then went through statistical analysis using IBM SPSS statistics analyzer v.23.0.Results: The current study used a total sample size of 88950 patients. Skeletal class 2 malocclusion was seen in 0.01 percent of cases overall. The data in this study was examined for the occurrence of different skeletal inconsistencies. Results were satisfactory and showed that there were skeletal differences. A gender bias was evident, with 50.4 percent of the sample population being female. Mandibular deficit was the most frequent skeletal discrepancy, and class 2 div 1 dental malocclusion was most frequently detected.Conclusion: Mandibular deficit was shown to be the most common skeletal discrepancy within the constraints of the current investigation, and a substantial correlation between the skeletal discrepancies and the gender of the study group was found.